Formando leitores literários no meio digital - Schabarum, Karine da Veiga (2020)
This article presents the process of transforming reading, book, literature to from the study about, the types of readers and their respective reading practices throughout the times, and reveals, in particular, to teachers possibilities of using tools in the formation of contemporary literary readers. This study was developed through bibliographic research based on studies on the characteristics of the reader contemporary, its reading practices and how they have changed in the digital age. Therefore, authors such as Santaella (2004, 2013) and Lèvy (1996, 2003) were used for the deepening of the theme. As final considerations, it is clear that continuing education of teachers is essential for the understanding and transformations of pedagogical practices to appropriation of digital tools that assist in the formation of the contemporary reader.